HOUSEWIFE FINANCIAL PROCESSING TRAINING IN TIGARUNGGU - Diana Florenta Butar-Butar; Nurmala; Yunardi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Community Service Managing Household Finances aims to improve financial management, especially for mothers in Tigarunggu. Based on an initial survey of 19 respondents, it was found that the level of financial management for mothers in the Tigarunggu Village Office, Simalungun Regency, was still low and had to be improved. As many as 19 household groups have not managed their finances properly. the recording carried out is still very limited, namely only recording income and expenses for housewives. Service method using counseling and qualitative analysis. The results of the service, after the pre-test and post-test were carried out, from 15 extension participants, the results obtained were that all 15 participants had understood managing household finances.